2016
DOI: 10.18203/2349-2902.isj20161162
|View full text |Cite
|
Sign up to set email alerts
|

Detection of medical errors in management of traumatic hypovolemic shocked adult patients presented to emergency department in Suez Canal university hospital, Ismailia, Egypt

Abstract: Background: IN 2010, Institute of Medicine in USA report that medical errors are estimated to result in about between 44,000 and 98,000 preventable deaths and 1,000,000 excess injuries each year in U.S. hospitals. The annual cost of treating medical injuries in USA has been estimated to be $9 billion. The objective of this study was to follow up guidelines in treatment of Traumatic hypovolemic shocked patients. Methods: The design of this study is a cross sectional descriptive study was conducted on traumatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Many probable reasons could lead to ignoring the guidelines. It was shown that most of the physicians did not use systematic reviews and evidence-based information for practice; instead, this is the result of their contact with drug retailers and their previous practice habits (16,17). Also, for our center some reasons could be regarded for non-compliance.…”
Section: Discussionmentioning
confidence: 87%
“…Many probable reasons could lead to ignoring the guidelines. It was shown that most of the physicians did not use systematic reviews and evidence-based information for practice; instead, this is the result of their contact with drug retailers and their previous practice habits (16,17). Also, for our center some reasons could be regarded for non-compliance.…”
Section: Discussionmentioning
confidence: 87%